Penanaman Nilai Moderasi Beragama Melalui Pendidikan Multikultural bagi Anak Usia Dini: Instilling the Value of Religious Moderation Through Multicultural Education for Early Childhood - Yurii, Yurita Erviana; Lita, Lita (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
A multicultural nation of Indonesian tribes, religion, language, and culture has its own challenges in the practice of government, educated even policy decrees. Diversity has often led to conflict, so to anticipate this, the study is done politically charged and aimed at religious moderation to infuse the value of multicultural through education for early childhood. This research uses descriptive qualitative research. Data collection techniques were obtained through online questionnaires, interviews, and documentation. The subject of this research is the PAUD teacher in the city of Wonosobo and Majalengka. The results showed that the cultivation of religious moderation values through multicultural education for early childhood first begins with the initial understanding of teachers regarding the cultivation of religious moderation values and multicultural education. Then carried out through three ways, integration into the learning theme, and integration into school culture. The habituation aims to get the described child to recognize,  know, and understand that what he does every day is a part of the internalization of the value of discipline, selflessness, and responsibility.  Activities in the theme of learning are performed through the theme of love of my homeland and culture. Teachers can specify themes according to each agency's needs. The school culture is used to describe the vision of missions and the philosophical meaning of institutions. Because this is what helps young children get used to all sorts of things. Then eventually there will be a strong character in early childhood. Future researchers can continue research with a focus on the final results after implementing the values of religious moderation and multicultural education in the daily activities carried out by children. ABSTRAK Negara Indonesia yang multikultur dengan keragaman suku, agama, bahasa, dan budaya memiliki tantangan tersendiri alam praktik pemerintahan, pendidikan bahkan penentuan kebijakan. Tidak jarang keragaman tersebut berujung pada terjadinya konflik. Guna mengantisipasi terjadinya  hal tersebut, maka penelitian ini dilakukan yang betujuan untuk menanamkan nilai-nilai moderasi beragama melalui pendidikan multicultural bagi anak usia dini. Penelitian ini menggunakan jenis penelitian kualitatif yang bersifat deskriptif. Teknik pengumpulan data diperoleh melalui kuesioner online, wawancara serta dokumentasi. Subjek penelitian ini adalah guru PAUD di kota Wonosobo dan Majalengka. Hasil penelitian menunjukkan bahwa penanaman nilai moderasi beragama melalui pendidikan multicultural bagi anak usia dini terlebih dahulu diawali dengan pemahaman awal guru mengenai penanaman nilai moderasi beragama dan pendidikan multicultural. Selanjutnya dilakukan melalui 3 cara yaitu kegiatan pembiasaan, integrasi kedalam tema pembelajaran, dan integrasi kedalam budaya sekolah.  Kegiatan pembiasaan  betujuan untuk membiasakan anak mengenali, mengetahui dan memahami bahwa apa yang dilakukannya setiap hari adalah bentuk dari internalisasi nilai disiplin, kemandirian dan tanggungjawab. Kegiatan dalam tema pembelajaran dilakukan melalui tema cinta tanah air dan budayaku. Guru bisa menspesifikkan tema sesuai dengan kebutuhan masing-masing lembaga. Sedangkan budaya sekolah digunakan untuk menjabarkan visi misi serta makna filosofis lembaga, sebab inilah yang kemudian dapat membantu anak usia dini terbiasa dengan berbagai hal yang ada di sekolah, kemudian pada akhirnya akan terbentuk karakter kuat pada diri anak usia dini. Peneliti selanjutnya dapat melanjutkan penelitian dengan fokus pada hasil akhir setelah dilakukannya implementasi nilai moderasi beragama dan pendidikan multicultural dalam aktivitas harian yang dilakukan anak